IMPLIKASI PEMBIAYAAN HAJI TERHADAP STABILITAS EKONOMI DAN PSIKOLOGIS KELUARGA MUSLIM : KAJIAN HUKUM ISLAM DAN PSIKOLOGI KELUARGA - Mustika, Fahmi; Kodri, Muh.; Sakti, Bagas; Ayu, Sekar; Fahmi, Rulia (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This article examines the implications of Hajj financing on the economic stability of Muslim families in Indonesia. As Hajj requires a significant financial commitment, many families rely on Islamic financial products such as qardh (benevolent loan) or Hajj bailout funds provided by Sharia financial institutions. This study aims to explore how such financing schemes affect family financial planning and psychological well-being. Using a qualitative descriptive method, this research draws on normative Islamic legal principles and family psychology theories. Findings indicate that while Hajj financing can accelerate religious obligations and elevate social status, it also introduces new economic pressures, particularly when repayments are burdensome. From the perspective of Islamic family law, the husband's financial responsibility is central, but contemporary practice shows shared decision-making within the household. Psychologically, families may experience stress or anxiety related to debt, affecting interpersonal dynamics. The study highlights the need for better financial literacy and legal awareness to ensure that Hajj remains both a spiritual and economically sustainable journey.